1966 Excavations at the Dickson Mound : a Sepo-Spoon River burial mound in the central Illinois River Valley - Conrad, Lawrence Allan (My University, 1972)
Contents include: the Central Illinois Valley, the Dickson Mound, Larson Phase utilization of the site, analysis of the Larson Phase burial practices, and analysis of the Larson Phase burial association.
163 leaves : ill. ; 29 cm.
Keywords: Illinois --Antiquities.